Survey of feeding practices and supplement use among a subpopulation of horses in Selangor, Kuala Lumpur and Putrajaya - Mohamad Zulkifli Manisegaran, Nur Syamini (2017)
Horses require a well-balanced diet which includes all essential nutrients, such as carbohydrates, proteins, fats, vitamins and minerals. Several factors such as age, breed, weight, sex, category of exercise and life stage of the horse need to be taken into account when formulating horse feed. The right feeding practices that meet the energy and nutrition requirements of horses may reduce the possibility of occurrence of nutritional-related diseases and reduced performance. The objective of this study was to study the feeding practices and supplement use among a subpopulation of horses in Selangor, Kuala Lumpur, and Putrajaya. The study was carried out (i) to identify the supplement use in the diet of horses in Selangor, Kuala Lumpur, and Putrajaya, and (ii) to determine whether the feeding practices meet the energy and nutrition requirements of the horses. A total of 133 horses from six stables around Selangor, Kuala Lumpur, and Putrajaya were selected. The necessary data obtained through the survey was incorporated into the software CFC Horse Ration Formulation System to calculate the energy and nutrient requirements. The results showed that the digestible energy, crude protein, and lysine were insufficient for most of the stables. Besides that, most horses in most stables had acceptable calcium to phosphorus ratio in their diet. Majority of the stables used supplements in feeding the horses. However, certain use vitamins and minerals were given in excess or insufficient.